Affective Language in Student Peer Reviews: Exploring Data from Three Institutional Contexts - Wärnsby, Anna; Kauppinen, Asko; Aull, Laura; Leijen, Djuddah; Moxley, Joe (Journal of Academic Writing, 2018)
Although peer review is a common practice in writing classrooms, there are still few studies that analyze written patterns in students’ peer reviews across multiple institutional contexts. Based on a sample of approximately 50,000 peer reviews written by students at the University of South Florida (USF), Malmö University (MAU), and the University of Tartu (UT), this study examines how students formulate criticism and praise, negotiate power relations, and express authority and expertise in reviewing their peers’ writing. The study specifically focuses on features of affective language, including adjectives, expressions of suggestion, boosters and hedges, cognitive verbs, personal pronouns, and adversative transitions. The results show that across all three contexts, the peer reviews contain a blend of foci, including descriptions and evaluations of peer texts, directives or suggestions for revisions, responses to the writer or the text, and indications of reader interpretations. Across all three contexts, peer reviews also contain more positively glossed responses than negatively glossed responses. By contrast, certain features of affective language pattern idiosyncratically in different contexts; these distinctions can be explained variously according to writer experience, nativeness, and institutional context. The findings carry implications for continued research and for instructional guidance for student peer review.